2021
DOI: 10.1016/j.xrrt.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic marginal resection of a lipoma under the supraspinatus muscle: a case report

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In addition, a case report by Nakamura et al published in 2021 described a patient who presented with a case of lipoma under the supraspinatus muscle, which was located in the supraspinatus fossa where the suprascapular nerve runs. The authors reported successful arthroscopic resection of the lipoma combined with suprascapular nerve release [ 8 ]. In our case, the lipoma occurred deep to the deltoid muscle, concomitant with a subscapularis tear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a case report by Nakamura et al published in 2021 described a patient who presented with a case of lipoma under the supraspinatus muscle, which was located in the supraspinatus fossa where the suprascapular nerve runs. The authors reported successful arthroscopic resection of the lipoma combined with suprascapular nerve release [ 8 ]. In our case, the lipoma occurred deep to the deltoid muscle, concomitant with a subscapularis tear.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoma is one of the most common soft-tissue tumors; it is predominantly located in the subcutaneous tissues [14]. However, there are few reports that intramuscular lipoma in the supraspinatus muscle could be associated with subacromial impingement due to the thickening of the supraspinatus muscle [8][9][10][11]. In our case, the tumor was located adjacent to the subscapularis insertion, and the growing mass in this limited space could have compressed the subscapularis tendon, causing coracoid impingement and ultimately leading to the subscapularis tear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations